FACTORS ASSOCIATED WITH DEPRESSION AND ANXIETY IN YOUNG ADULTS IN METROPOLITAN CITY - Dian Restu Asih; Andi Nurhafidzah Hidayah Askin; Hoirun Nisa (Poltekkes Kemenkes Semarang, 2023)
Depression is estimated to be experienced by 12 million young adults. In 2021, the prevalence of depression among the people was estimated to be about 20% due to the Covid-19 pandemic. The use of social media can be a trigger for depression and anxiety, especially among young people who are very closely related to social media. In addition, other factors can contribute to depression and anxiety, such as working status, age, married status, and gender. Aim of study is to find factors that influence depression and anxiety in young adults. This study used a quantitative analytic observational approach with a cross-sectional which was carried out in September-October 2022. It involved 285 young adult respondents aged 18-25 years who had lived at least 1 year in a metropolitan area (Jakarta, Bogor, Depok, Tangerang, Bekasi). This study showed that depression (66.4%) and anxiety (73.3%) are quite high in young adults. Working status is significantly associated with depression (p=0.0001) and anxiety (p=0.0001). Similarly, duration of social media use is significantly associated with depression (p0.001) and anxiety (p=0.026). However, gender, age, and marital status are not associated with depression and anxiety.